Regulatory roles of SP-A and exosomes in pneumonia-induced acute lung and kidney injuries - Chen, Xinghua; Guo, Junping; Mahmoud, Salma; Vanga, Gautam; Liu, Tianyi; Xu, Wanwen; Xiong, Yunhe; Xiong, Weichuan; Abdel-Razek, Osama; Wang, Guirong (Frontiers in Immunology, 2023)
Pneumonia-induced sepsis can cause multiple organ dysfunction including acute lung and kidney injury (ALI and AKI). Surfactant protein A (SP-A), a critical innate immune molecule, is expressed in the lung and kidney. Extracellular vesicles like exosomes are involved in the processes of pathophysiology. Here we tested one hypothesis that SP-A regulates pneumonia-induced AKI through the modulation of exosomes and cell death. Wild type (WT), SP-A knockout (KO), and humanized SP-A transgenic (hTG, lung-specific SP-A expression) mice were used in this study. After intratracheal infection with Pseudomonas aeruginosa, KO mice showed increased mortality, higher injury scores, more severe inflammation in the lung and kidney, and increased levels of serum TNF-α, IL-1β, and IL-6 compared to WT and hTG mice. Infected hTG mice exhibited similar lung injury but more severe kidney injury compared to infected WT mice. Increased renal tubular apoptosis and pyroptosis in the kidney of KO mice were found when compared with WT and hTG mice. We found that serum exosomes from septic mice cause ALI and AKI through mediating apoptosis and proptosis when mice were injected intravenously. Furthermore, primary proximal tubular epithelial cells from KO mice showed more sensitivity than those from WT mice after exposure to septic serum exosomes. Collectively, SP-A attenuates pneumonia-induced ALI and AKI by regulating inflammation, apoptosis, and pyroptosis; serum exosomes are important mediators in the pathogenesis of AKI.